Development of Elementary School Social Competence Questionnaire and Analysis of Its Psychometric Characteristics - Magelinskaitė-Legkauskienė, Šarūnė; Legkauskas, Visvaldas; Kepalaitė, Albina (Pedagogika, 2017)
While social competence is widely studied, relatively few studies are aimed at investigating social competence at elementary school years. Furthermore, social competence tends to be dependent on social and cultural context; hence instrument developed in one country may require significant adaptations in other countries. Thus, the purpose of the present study was to develop a Lithuanian questionnaire for assessment of social competence at elementary school. Individual items for the Elementary School Social Competence Questionnaire were drawn from the Early Developement Instrument (Janus et al., 2007), the Social Emotional School Readiness Scale (Bustin, 2007), and the Social Competence Inventory (Rydell et al., 1997). The study was conducted in two waves. In the first wave subjects were 437 first graders (198 boys and 239 girls) from Lithuania. In the second wave, which took place a year after, 192 boys and 228 girls participated. The Elementary School Social Competence Questionnaire was developed from the initial pool of items using structural equation modeling. The Questionnaire contained the Communicative Social Competence Subscale and the Ability to Take Directions Subscale. The initial measurement model was confirmed using confirmatory factor analysis on the dataset obtained during the second wave of measurement. Both subscales demonstrated good internal and test-retest reliability. Construct validity of the instrument was assessed by correlating its subscales with student-teacher relationship, in-class popularity, and school anxiety measures.